COMPARATIVE DIAGNOSTIC APPLICATIONS OF ANTIGEN CAPTURE ELISA AND IMMUNOHISTOCHEMISTRY FOR DETECTION OF BOVINE VIRAL DIARRHEA PERSISTENT INFECTION - A. Ahmad; M. Rabbani; K. Muhammad; M. Younus; M. Z. Shabbir; A. Ghafoor; A. A. Anjum; J. Nazir; M. K. Saleemi; J. Muhammad; A. A. Ali; A. Cepica (Journal of Animal and Plant Sciences, 2014)
The diagnostic ability of antigen-capture enzyme-linked immunosorbent assays (AC-ELISA) and immunohistochemistry using two enzymes labels, alkaline phosphatase (AP) and peroxidase (P), to detect bovine viral diarrhea (BVD) persistent infection (PI) was assessed using serum and ear notch biopsy pairs (n= 469) collected from 12 Holstein dairy herds located in Charlottetown, Canada. The sampled animals were divided into two age groups, A (≤ 6 months, n = 146) and B (≥ 6 months, n = 323). All the animals of group B were pre-screened by serum neutralization test (SNT), and those animals (n=52) which had SN titer ≤ 1:64, as well as all ear notch biopsies (EN) of group A (n=146) were processed to confirm the BVDV persistent infection. Two EN biopsies of each groups A (1.37%) and B (3.48%) were found positive on first and follow up testing by AC-ELISA and immunohistochemical technique using AP enzyme label. Peroxidase label could not be distinguished from skin melanin, and thus was found unsuitable to differentiate between positive and negative tissue sections. There was no significant difference (P>0.05) between AC-ELISA and IHC-AP.  Real time RT-PCR validated the results as well. Genotype 1 was confirmed in the study area. The study concluded that AC-ELISA and IHC-AP were equally suitable for detection of BVDV persistent infection.
Keywords: Prevalence; Bovine Viral Diarrhea Virus; Persistent infection; AC-ELISA; IHC